Major Sesquiterpenes of Patchouli Leaf Essential Oil (Pogostemon cablin Benth.): A GC-MS Study - Taupik, Muhammad; Adam Mustapa, Mohamad; Radjak, Fahmi As; Andy Suryadi, A. Mu'thi; Aprianto Paneo, Mohamad (Jurnal Literasi Mandiri, 2025)
Patchouli (Pogostemon cablin Benth.) is a tropical plant widely recognised as the main source of patchouli oil, an essential oil with high economic and pharmaceutical value. This study aimed to identify the chemical constituents of patchouli leaf essential oil and determine its major compounds. Extraction was performed using solvents of different polarities, followed by analysis with Gas Chromatography–Mass Spectrometry (GC-MS). The results revealed five dominant compounds: Bicyclo[5.3.0]decane, 2-methylene-5-(1-methylvinyl)-8-methyl (19.99%), Aromandendrene (12.04%), Naphthalene, decahydro-4a-methyl-1-methylene-7 (9.20%), Caryophyllene (7.29%), and Valerena-4,7(11)-diene (6.87%). These compounds play an important role in both the aroma and biological activities of patchouli oil. Methanol, as a polar solvent, produced the highest yield (10%), while n-hexane yielded the lowest (2%). The findings confirm the potential of patchouli essential oil as a natural source for pharmaceutical, cosmetic, and aromatherapy applications.